The Importance of Clinical Data & Prevalence of Breast Tumors in South Punjab, Pakistan - Fawad Hameed, Javeria Afzal, Ahmad Rafique, M Khurram Jameel, Khurram Niaz, Humiara Alam, Muhammad Shoaib, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In Western countries, middle-aged women are more vulnerable to breast cancer. Globally, almost a million new cases were identified in 1998. One in 12 women in England and Wales will get the disease at some point.1 Even 5,000 years after it was first reported, the etiology of breast cancer is still unclear, and effective preventative measures are even further off. Aim: To characterize the varied ways in which breast cancer has presented itself among patients at Bahawal Victoria Hospital in Bahawalpur. Methods: This investigation employed a descriptive case series research design. This research was conducted at Bahawal Victoria Hospital's Surgery Department in Bahawalpur (Pakistan). From March 13th, 2020 through March 12th, 2021, the study was conducted (12 months). With their assent, 100 women with definite cases of breast cancer were enrolled in the study. Results: Cancer of the breast most commonly affected women between the ages of 31 and 50 (59%). Seventy-six patients arrived from the outlying rural areas of Bahawalpur and the neighboring districts. Only 18 patients had completed high school after 10 years and 5 patients were discovered to be college graduates. The single rate was 12%, with 12 patients. Eighty-one percent of patients reported having a breast lump. 56% of breast cancers involve the left breast, while 43% involve the right. One patient alone had breast cancer that had spread to both of her breasts. Illness duration varied from 1 month to 5 years. Stage III was the most prevalent presentation, with 46 instances, and Stage IV was the least common, with 16 patients. Practical implication Community based effective awareness and prompt screening programme will improve better outcomes in breast cancer management. Conclusion: Breast cancer is very common cancer in the females, and most commonly it presented as a lump in the breast, because of some social aspects, lack of awareness, poverty, no proper screening programs and above all the fear of diagnosis, females try to hide this problem and often it presented at late and more advance stage. Keywords: Breast, Nipple, Cancer, Lump, Surgery, Tumor